Analisis Pesan Dakwah Ustadz Khalid Basalamah “Membangun Keluarga Islami” di Media Sosial Instagram - Randa Aditia; Muhammad Husni Ritonga (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study attempts to find out the family da'wah message conveyed by Ustadz Khalid Basalamah via Instagram, especially regarding the da'wah strategy carried out by men towards their wives and vice versa. The methodology used is a qualitative approach using content analysis techniques. The findings of the study indicate that Ustadz Khalid Basalamah proposed two different da'wah tactics in husband-wife relationships. The husband's da'wah to his wife uses the sentimental method (al-manhaj al-a'thifi), including three models: da'wah with hugs, da'wah with tenderness, and da'wah with steadfastness. Meanwhile, the wife's da'wah to her husband uses a reasonable technique (al-manhaj al-'aqliy), which is divided into two models, namely da'wah through inquiry and da'wah through narrative. These findings increase understanding of efficient methods for conveying da'wah messages in families through good and logical communication.